Some Fungi as Wound Parasites on Indian Trees - Bagchee, K.; Bakshi, B. K. (Indian Forester, 1950)
The paper is intended to point out the dangers that arise due to maltreatments inflicted on our trees in avenues, parks and forests. Uncontrolled lopping of trees results in injuries through which fungi gain entrance into hosts. Seven such important fungi, namely, Polyporus gilvus (Schw.) Fr., Ganoderma lucidum (Leyss.) Karst., Ganoderma applanatum (Pers.) Pat., Fomes badius Berk., Fomes rimosus Berk., Fomes senex Nees and Mont. and Fomes pini (Thore.) Lloyd., have been described as they occur in nature as well as in culture and their pathology on important Indian trees has been discussed. The fungi are major heart rotting organisms and since the sapwood is not attacked, at any rate in the early stages, the infected trees continue to live until blown down by wind. It is needless to emphasize the difficulty of replacing these wind thrown shade trees along avenues where they are subject to adverse soil, moisture and weather conditions to which they are not exposed in their natural surroundings. Decay of the heartwood causes serious loss in timber and other economic products while attack in the sapwood tones down the general vitality of the trees and they are ultimately killed. To safeguard trees from attack by wound parasites, therefore, all such malpractices should be stopped. Methods have been discussed as to how to protect trees from attack by wound parasitic fungi.